1994
DOI: 10.1165/ajrcmb.10.2.8110476
|View full text |Cite
|
Sign up to set email alerts
|

Detection of rhinovirus infection of the nasal mucosa by oligonucleotide in situ hybridization.

Abstract: Human rhinoviruses (HRVs) cause the common cold and often induce lower airway symptoms such as cough and wheezing. Although HRV infection is presumed to involve primarily ciliated epithelial cells, this has not been confirmed in vivo, and the cellular distribution and spread of infection as well as the pathogenesis of cold related nasal and chest symptoms remain speculative. We have developed in situ hybridization (ISH) to explore localization of the virus to airway tissues, employing HRV 16-derived oligonucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
49
1
3

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(59 citation statements)
references
References 0 publications
6
49
1
3
Order By: Relevance
“…Although epithelial cells are the main target for HRV infection, several studies have indicated that HRV may be detected in the subepithelial layer by in situ hybridization (8,9) and that human lung fibroblasts are susceptible to HRV infection (10). Bronchial fibroblasts are part of the mesenchymal layer in the airway tissue and have the versatility to differentiate into other connective tissue families such as smooth muscle cells and myofibroblasts (11).…”
Section: H Uman Rhinoviruses (Hrv)mentioning
confidence: 99%
“…Although epithelial cells are the main target for HRV infection, several studies have indicated that HRV may be detected in the subepithelial layer by in situ hybridization (8,9) and that human lung fibroblasts are susceptible to HRV infection (10). Bronchial fibroblasts are part of the mesenchymal layer in the airway tissue and have the versatility to differentiate into other connective tissue families such as smooth muscle cells and myofibroblasts (11).…”
Section: H Uman Rhinoviruses (Hrv)mentioning
confidence: 99%
“…The airway epithelial cell is the dominant site of HRV infection in vivo (5,6), and both upper and lower airway epithelial cells are infected at a similar frequency (7). HRV infections do not lead to overt changes in epithelial cell integrity or viability, but they can induce epithelial production of a number of chemokines and cytokines (8 -11).…”
mentioning
confidence: 99%
“…Moreover, it has been shown that virus also spreads to the lower airway epithelium (3,35). In contrast to some other viruses, HRV does not induce overt epithelial cytotoxicity.…”
mentioning
confidence: 99%